The Strategic Leadership Management of the Luxury Hospitality Industry: An Examination of Organisational Effectiveness by Utilising Integrated Leadership Principles - Kemrichard, Pattisan (Global journal of Business and Integral Security, 2024)
According to the context of unprecedented global changes and challenges, particularly those spurred by the COVID-19 pandemic, all industries worldwide must reconfigure their strategic management principles to regain their competitive edge. This research focuses on the Luxury Hospitality Business (LHB) sector in Thailand, which is notably affected by global health crises and economic shifts. This quantitative examination of the study aims to investigate the current strategic leadership management practices employed by LHB in Thailand, identify potential gaps, and propose suggestions for improved strategies to regain their lead in the evolving hospitality landscape. The research justifies its examination of LHB's leadership principles within three leadership disciplines: Transformational Leadership (TL), Sustainability Leadership (SL), and Resilient Leadership (RL). The investigation seeks to identify aspects of Job Satisfaction (JS) and Employee Engagement (EE) within the Thailand-based LHB sector. The study recommends the implementation of an Integrated Strategic Leadership Management System (ISLMS) that encompasses various leadership roles within the organisation. The goal of the ISLMS is to cultivate an environment that fosters innovation and creativity, expedites the adoption of new initiatives and technologies, and prepares the organisation for present and future challenges. The ISLMS model encourages multidisciplinary perspectives of multi-level executives, fostering long-term growth within the LHB sector in Thailand. Primary data will be derived from corporate commercial reports focusing on hospitality leadership principles from established hospitality brands and prior quantitative research articles and journals, namely Google Scholar, ResearchGate, Elsevier, and various Institutional Research Portals. Secondary data will be collected via surveys with multidisciplinary and multi-level executive positions in the Luxury Hospitality Business in Thailand and will be tested quantitatively.